Предмет: Алгебра,
автор: ппее1
решите уравнение: (х+11)(х+9)-(х-3)(х+40)=0
Ответы
Автор ответа:
3
(x+11)(x+9)-(x-3)(x+40)=0
x²+9x+11x+99-x²+40x-3x-120=0
x²+9x+11x-x²+40x-3x=0-99+120
57x=21
x=21/57
x=7/19
x²+9x+11x+99-x²+40x-3x-120=0
x²+9x+11x-x²+40x-3x=0-99+120
57x=21
x=21/57
x=7/19
Автор ответа:
1
вроде так......................
Приложения:
Похожие вопросы
Предмет: Другие предметы,
автор: rorat65
Предмет: География,
автор: celjdfkmytr
Предмет: Английский язык,
автор: jailler
Предмет: Математика,
автор: igorromanyuk8